A percepção de confiança do usuário sobre as medidas de segurança entre transporte público e por aplicativos: um estudo de caso com os discentes da UFAM - Melo, Daniel Marreiro (Brasil, 2024)
This study addresses the integration of services between the public transport market and applications with effective measures in the flow of users for journeys involving home or work to UFAM. Notably, digital platforms suggest the popularity and predominance of transformation in culture among young people and the visualization that safety can influence the choice of transport among users. In this aspect, the aim of investigating through questionnaires in Google Forms format was to raise the issue of how security measures between transport services point to implications for describing the portrait of the impacts they generate on students. The research was carried out on samples of 100 UFAM students, of which the participants gave their opinion on the topic. The importance of this research refers to the impact that companies like Uber, 99 and inDrive have on citizens' routines. In this sense, safety is one of the determining factors in users' choice between different means of transport, especially with regard to the vulnerability of women, who face risks such as harassment and violence when using these services. From the results, it is highlighted that the interference of these improvements in transport through applications helps users to increase their confidence and respect the commitments that applications require. At the moment, public transport is making attempts to get closer to the competition to meet demand and increase users' confidence in the safety factor.